The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/aheh.200400566
|View full text |Cite
|
Sign up to set email alerts
|

Bulking and Foaming in France: The 1999–2001 Survey

Abstract: Surveya Wastewater Treatment, To assess bulking in French wastewater treatment plants we developed a three-topic Water Quality and Hydrology approach, including analysis of i) technical assistance annual reports, ii) a questionnaire, Research Unit, Cemagref, and iii) microscopic sample observations. A seasonal effect was very apparent on the Parc de Tourvoie BP 44, F-92163 Antony cedex, France average SVI (mL/g). Three situations appear to promote bulking according to statistical analysis and operators' commen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…However, they found that a Microthirx bacterium, which is one of the most common filamentous bacteria, was most abundant in winter, although they did not observe a clear, seasonal variation in the filaments [24]. Graveleau et al [13] found no significant seasonal differences in terms of micro-organism population distribution, although they found a seasonal pattern in SVI values. However, Flowers et al [25] found that temperature was the environmental variable that best correlated with changes in bacteria species and that bacteria species cycled through a predictable, seasonal pattern yearly, which confirms the results of the present study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, they found that a Microthirx bacterium, which is one of the most common filamentous bacteria, was most abundant in winter, although they did not observe a clear, seasonal variation in the filaments [24]. Graveleau et al [13] found no significant seasonal differences in terms of micro-organism population distribution, although they found a seasonal pattern in SVI values. However, Flowers et al [25] found that temperature was the environmental variable that best correlated with changes in bacteria species and that bacteria species cycled through a predictable, seasonal pattern yearly, which confirms the results of the present study.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, previous studies [13,24,25] have sought to identify seasonal patterns in micro-organism populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,16, 19 En las PTAR el IVL es el indicador determinante de la presencia de bulking con un valor límite de 150 mL/g, no obstante el diseño de las PTAR en países como Francia, por ejemplo, permite valores hasta de 200 mL/g, siendo este el valor considerado en ese país, como el umbral más allá del cual un tanque de sedimentación no puede garantizar la adecuada separación de lodos. 18 La baja concentración de OD fue uno de los parámetros con mayor influencia en la proliferación de bacterias filamentosas, lo cual puede explicarse debido a que este grupo de microorganismos posee mayor superficie/volumen que las bacterias formadoras de floc, proporcionándoles una ventaja en la obtención de oxígeno disponible. Un lodo activado en condiciones normales generalmente tiene un OD igual o mayor a 2 mg/L, niveles que permiten controlar la proliferación de estas bacterias.…”
Section: Discussionunclassified
“…Furthermore, it was measured that, in typical Danish wastewaters, the diluted SVI (DSVI) value of 120 ml/g and above suggests a poorly settling sludge (Mielczarek et al, 2012). Moreover, Graveleau et al (2003) observed bulking at an SVI value of 180 ml/g and above. Some studies assess the total extended filament length (e.g.…”
Section: Introductionmentioning
confidence: 99%